Alginate–copper microspheres as efficient and reusable heterogeneous catalysts for the one-pot synthesis of 4-organylselanyl-1H-pyrazoles. Issue 12 (5th June 2020) - Souza, Jaqueline F.; de Aquino, Thalita F. B.; Nascimento, José E. R.; Jacob, Raquel G.; Fajardo, André R.
Abstract : This study demonstrates the facile preparation and use of alginate–Cu 2+ microspheres in the catalysis of a new class of organoselenium substituted pyrazoles through one-pot reactions. Abstract : Polysaccharide-based materials have been claimed as efficient supports for different species used in catalysis, such as transition metal ions. Overall, the immobilization of metal ions on these materials brings several attractive aspects in terms of economy and catalytic activity. In this study, we demonstrated the facile immobilization of Cu 2+ ions on alginate-based microspheres (Alg–Cu 2+ ) via a straightforward ion exchange process. The prepared microspheres were characterized in detail by different techniques. As assessed, the ion-exchange process promoted some change in the properties of the microspheres, which was ascribed to the strong interaction forces established between the alginate matrix and Cu 2+ ions. The catalytic activity of Alg–Cu 2+ was investigated towards the one-pot synthesis of 4-organylselanyl-1 H -pyrazole derivatives via cyclocondensation reactions of diketones and hydrazines, followed by direct selenation reactions. In general lines, the starting reagents were efficiently converted via one-pot reactions to different derivatives in moderate to excellent yields. Moreover, the Alg–Cu 2+ catalysts still maintained satisfactory catalytic activity even after five consecutive runs. These results indicate that the Alg–Cu 2+ microspheres prepared in this study are a promising heterogeneous catalytic system for the synthesis of this class of substituted pyrazoles.